Variasi Genetik Mutan Anggrek Spathoglottis plicataBlume. Berdasarkan Marker ISSR - Atra Romeida; Surjono Hadi Sutjahjo; Agus Purwito; Dewi Sukma; , Rustikawati (Indonesian Journal of Agronomy, 2012)
Mutants of Spathoglottis plicataBlume were obtained from plants treated with Gamma Irradiation at 30-100 Gray. The mutants showed variations in the flower morphology. The objective of this experiment was to identify genetic variations of orchids S. plicataand its mutants using inter-simple sequent repeat (ISSR) markers. The amplified product of 10 ISSR primers produced 360 bands and 71 ISSR of the loci (90.14%) were polymorphic. The coefficient of similarity and principal component analysis produced five major groups with similarity coefficient of 0.68. The goodness of fit correlation matrix value reached 0.91. Therefore the ISSR isa good marker for identification of S. plicatamutants.Keywords: gamma irradiation, ISSR marker, mutant, orchid